Corporate governance : a synthesis of theory, research, and practice - Anderson, Ronald; Baker, H. Kent (The Robert W. Kolb series in finance, 2010)
This title provides a detailed look at the importance of corporate governance in today's business world. The book addresses essential issues related to corporate governance including the idea of principal-agent conflict, the role of the board of directors, and much more